2017
DOI: 10.1371/journal.pone.0180489
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression patterns of cell cycle regulators in operable breast cancer

Abstract: Background-AimTo evaluate the prognostic role of elaborate molecular clusters encompassing cyclin D1, cyclin E1, p21, p27 and p53 in the context of various breast cancer subtypes.MethodsCyclin E1, cyclin D1, p53, p21 and p27 were evaluated with immunohistochemistry in 1077 formalin-fixed paraffin-embedded tissues from breast cancer patients who had been treated within clinical trials. Jaccard distances were computed for the markers and the resulted matrix was used for conducting unsupervised hierarchical clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…Prabhu et al reported that overexpression of p21 in human osteosarcoma cells protected against etoposideinduced cell death [31]. Zagouri et al reported that overexpression of p21 was associated with a poor prognosis of breast cancer patients [32]. P21 protein is still regarded as a protein with dual behavior, as its expression can be beneficial or disadvantageous in patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Prabhu et al reported that overexpression of p21 in human osteosarcoma cells protected against etoposideinduced cell death [31]. Zagouri et al reported that overexpression of p21 was associated with a poor prognosis of breast cancer patients [32]. P21 protein is still regarded as a protein with dual behavior, as its expression can be beneficial or disadvantageous in patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…CCND1 contributes to tumorigenesis through crosstalk with the retinoblastoma tumor suppressor protein and alteration of cell cycle phases. Mutation and overexpression of CCND1 are frequently observed in various cancer types 39 - 41 . IRS-1 is a substrate of the insulin receptor tyrosine kinase, and its high expression is correlated with low tumor cell invasiveness in some cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…3). CCND1, CCNE1 and BCL‐2 proteins are involved in cell cycle advancement and are often overexpressed in cancer (26–28). Although the best‐described function of MSH‐2 is in the DNA mismatch repair system, other functions have been ascribed to this protein (29).…”
Section: Discussionmentioning
confidence: 99%